Corruption and economic growth: Does the size of the government matter? - António Afonso; Eduardo de Sá Fortes Leit\~ao Rodrigues (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
Corruption is often a source of contentious debate, covering different areas of knowledge, such as philosophy and sociology. In this paper we assess the effects of corruption on economic activity and highlight the relevance of the size of the government. We use dynamic models and the Generalized Method of Moments (GMM) approach for a panel of 48 countries, from 2012 to 2019. We find an adverse effect of corruption on the level and growth of GDP per capita, but that large governments benefit less from reducing corruption. Furthermore, developing economies, regardless of government size, benefit less from reducing corruption, while government size is not sufficient to explain the influence of corruption on economic activity, although the level of effectiveness of public services is crucial. Finally, our findings suggest that private investment is a potential transmission channel for corruption.
Keywords: C23; O40; K42; C23; 330; Corruption; Economic Growth; Government Size; Generalized Method of Moments; Forward Orthogonal Deviations